Environmental Racism in the Accessibility of Urban Green Space: A Case Study of a Metropolitan Area in an Emerging Economy - Bressane, Adriano [UNESP]; Loureiro, Anna Isabel Silva [UNESP]; Negri, Rogério Galante [UNESP] (MDPI, 2024)
Urban Green Spaces (UGS) are integral to advancing urban sustainability and improving the quality of life in cities. However, in rapidly urbanizing regions like the São Paulo Metropolitan Region (MRSP), significant environmental injustices in UGS accessibility present a complex challenge that requires in-depth understanding. Notably, existing studies predominantly focus on developed countries, leaving a gap in research concerning emerging economies in the Global South. This study aims to analyze the associations between sociodemographic factors and environmental racism in UGS accessibility within the municipalities of MRSP. The research utilizes Spearman Rank Correlation and multiple linear regression analyses on data sourced from the Brazilian Institute of Geography and Statistics and the Urban Green Data Platform. Key variables include the number of inhabitants, territorial area, population density, urbanization rate, gross domestic product (GDP), human development index (HDI), urban vegetation coverage, UGS per capita, and the difference between the total population and the Black or Indigenous populations residing outside the vicinity of UGSs as an indicator of environmental racism. The findings reveal significant correlations between higher GDP and HDI with increased environmental racism in UGS accessibility, suggesting that, in the absence of equitable policies, economic and human development may exacerbate disparities in green space distribution. Moreover, the study demonstrates that increased urban vegetation coverage is significantly associated with reduced environmental disparities, underscoring the role of urban greenery in mitigating inequality. These results emphasize the need for comprehensive urban planning and targeted policies that prioritize the equitable development of UGS, particularly in underserved areas. Future research should explore longitudinal data to establish causality and consider additional variables such as political governance and cultural factors, which could provide a more comprehensive understanding of environmental racism in UGS accessibility.
Keywords: emerging economies; environmental racism; metropolitan regions; sociodemographic factors; urban green spaces